NAVIGATING THE INTERSECTION OF AI IN EDUCATION: DIFFERENTIATED ASSESSMENTS AS A PEDAGOGICAL REFORM - Cruz, Mary; Kostadinovic, Bojan; Provodnikova, Anna (Global journal of Business and Integral Security, 2024)
The 21st century with the intersection of AI and Education offers great opportunities to educators and learners. This changing scenario can be navigated with new and varied pedagogical reforms. Technology 4.0 should bring out fast paced educational reforms. The research primarily focussed on a differentiated assessment system so that the creative and critical thinking can be evaluated. This assessment was learner centric rather than teacher centric; it explored a novel method of quantifying skill progress rather than route memorisation. This research aimed to develop creative thinking in graduates by implementing a differentiated assessment pattern based on the ACER creative thinking framework. The age of rapid automation and AI poses a threat to low-skilled labour; therefore educational institutions must focus more on developing skills that machines cannot replicate. The exploratory case study over a longitudinal period of six months concluded that a concept called as flip question paper, in the form of science fiction writing and white paper projects develop higher-order thinking skills in graduate learners. Though the variance in strengths of learners is a well-established fact most assessments sill follow a standardised pattern rather than differentiated . This study was also able to quantify data from the assessment so that transcripts can have creative and critical thinking mapped along with domain knowledge